Junior College Articulation Conference, November 8, 1968 - Robert E. Kennedy::::::::: (1968)
[00:00:00] Dale Andrews explains why he is dressed so casually for the affair [00:01:31] Andrews describes the literature materials that the audience has to reference through the conference [00:03:40] Andrews says that many attending Junior Colleges would like to interview their former students at Cal Poly [00:05:56] Man answers a question about meeting times [00:06:31] Andrews runs through the schedule for the conference [00:07:33] Andrews introduces Robert E. Kennedy [00:08:36] Kennedy makes a joke about how Andrews got injured playing sports with the Administration members [00:11:05] Kennedy states the goal of the conference that the schools can become more compatible with each other's curriculum [00:13:50] Kennedy applauds the Junior Colleges' Terminal Programs and the College Preparatory Program [00:15:15] Kennedy talks about the number of Junior College transfers at Cal Poly [00:17:30] Kennedy states his belief in the importance of disagreement and a healthy dissenting minority that pushes improvement [00:20:00] Kennedy talks about the importance of communication and the impossibility of pleasing everyone [00:22:19] Kennedy says that finding students that fit your particular institution is more important that simply recruiting [00:23:03] Kennedy reads a quote regarding polytechnic colleges and specialization [00:25:01] Audience claps at the end of Kennedy's speech [00:25:14] Dean George Mulder begins to speak on identifying potential Cal Poly students [00:25:39] Mulder talks about his experience as a counselor at Cal Poly Pomona and San Luis Obispo [00:26:49] Mulder talks about the difference between working at a Junior College and Cal Poly [00:28:20] Mulder hopes that the counselors in the audience will be able to truly tell their students what Cal Poly is like [00:30:07] Mulder talks about GPAs of struggling transferring students [00:31:15] Mulder talks about academic correlations between similar tests and grades and Cal Poly and the Junior Colleges [00:32:50] Mulder explains the guidance test that Cal Poly utilizes [00:34:50] Mulder tells the audience to look at the manner in which Cal Poly's curriculum is set up [00:35:32] Mulder talks about the pragmatic overview of the different schools at Cal Poly, particularly the engineering and arts schools [00:36:56] Mulder says he does not think there is a difference in identifying students for Cal Poly's arts or science other than the pragmatic overview [00:37:53] Mulder talks about the climate of San Luis Obispo, weather, culture, politics, women's security [00:39:10] Mulder talks about the things that Cal Poly 'is not' - no undeclared major, not a liberal arts school, not a technical institute [00:41:10] Mulder talks about the reasons Cal Poly has maintained a small college feeling [00:43:56] Mulder addresses on campus housing and housing near the Cal Poly campus [00:44:44] interference from other side of tape heard in left ear [00:45:39] David Cook begins to speak about the General Education requirements [00:47:20] Cook discusses the State Colleges new General Education pattern that students must satisfy [00:49:07] Cook explains the requirements of the new GE pattern [00:50:09] interference from other side of tape heard in left ear [ends at 50:46] [00:50:20] Cook states that Cal Poly specifies the minimum and maximum GE courses for each area [00:52:26] Cook specifies a new change to the 'Humanities' section for GEs [00:53:24] Cook explains which course can count as a GE course for each of the subjects natural sciences and social sciences [00:55:45] Cook states ow transfer students can satisfy GE requirements via testing or course equivalency [00:56:40] Cook discusses the Humanities GE requirements [00:57:40] Cook states that Cal Poly is maintaining its math requirement and communication requirement [00:58:24] Cook explains the area of 'Other Subjects' [01:00:25] Cook says that the representatives of each major curriculum will decide for the student which courses will count toward general education patterns [01:04:50] Donald Coats begins to speak on easing the transfer from junior college [01:05:38] Coats defines articulation as the relationship between the different elements of the educational system [01:06:34] Coats admits that Cal Poly will not have a program applicable for every student [01:08:24] Coats says that Cal Poly has formal articulation agreements with most of the California Junior Colleges [01:09:12] Coats says that an articulation agreement is essentially a course equivalency agreement that tells which courses at the Junior Colleges are similar to courses at Cal Poly